Manajemen Pemeliharaan Rumah Kos dari Pihak Pemilik dan Pengelola: Survey - Monik Karlina (Jurnal Proyek Teknik Sipil, 2022)
A survey was conducted of 12 boarding houses spread across Ciwaruga, West Bandung Regency to investigate their current maintenance practices and property management functions. This finding highlights the policies of boarding house managers and owners regarding boarding house management planning; the extent of planning for budgeting; how to promote boarding rooms; by what means the rent is collected; a good relationship with the tenant; boarding house operational costs incurred; and the use of preventive/routine/deferred/emergency maintenance. Owners and managers of boarding houses should be aware of the concerns of tenants and they should also make designers aware of these issues; Building performance is likely to be improved if boarding house owners and managers take action in the design and operation phases in response to tenants' concerns.